Character-Based Affective Assessment Concept in Modern Learning in Elementary School - M. Hulkin; Shaleh (Jurnal PAJAR (Pendidikan dan Pengajaran), 2024)
Character formation in fostering attitudes and values in modern learning contexts has become a very central topic in research or discussions focusing on the use of affective assessment as a tool to measure and also describe these aspects in education. The research purpose is to determine the concept of character-based affective assessment to foster attitudes and values in modern learning and integrate affective assessment approaches in curriculum and teaching methods to effectively enhance positive character formation and the development of desired values in the context of modern era-oriented education. This research uses the literature study method, as well as analyzing existing data. The research results provide valuable insights into how the concept of character-based affective assessment can play a role in fostering attitudes and values in modern learning. It aims to create individuals who are not only academically intelligent but also have positive values and good attitudes to contribute positively to society. This research has important implications for enhancing students' character development through affective assessment, improving positive attitudes, contributing to the improvement of educational values, developing character teaching guidelines, and supporting the development of students' leadership skills.